The Influence of SAVI (Somatic, Auditory, Visual, and Intellectual) Learning Model Activities In Improving Student’s Speaking Skills - Napitupulu, Leni Mardiah; Rahman Hz, Benni Ichsanda (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
This study intends to assess the oral communication proficiency of second-grade students at MTs Nurul Islam in Indonesia. This research utilised the Classroom Action Research methodology. The Class VIII students of the 2024–2025 academic year at MTs Nurul Islam Indonesia represent both the population and the sample. The purpose of this research is to find out how well the SAVI (Somatic, Auditory, Visual, and Intellectual) Technique works for improving the public speaking abilities of eighth graders at MTs Nurul Islam Indonesia. The purpose of this research is to find out how well the SAVI method works for enhancing students' ability to speak in front of an audience. The study's population comprised seventeen eighth-grade students from MTs Nurul Islam Indonesia. To demonstrate the effectiveness of SAVI in enhancing students' speaking abilities, researchers collected quantitative data that met the KKM Minimum Completeness Criteria. This information was derived from the data of Cycle I and Cycle II. Only one student attained success (6% success rate) and one student encountered failure (6% failure rate) on pre-test I. During the initial cycle, 5 students achieved a success rate of 29%, no students failed, and 2 students received a satisfactory score of 12%. Nine students, representing 53% of the total, successfully passed post-test II in cycle II, with no failures noted. Subsequently, eight students, representing 47% of the total, were categorised as proficient in their English speaking abilities. The outcomes demonstrated by the students following the intervention substantiate the assertion that the SAVI method significantly improves students' speaking abilities.